Smallholder mechanization induced by yield-enhancing biological technologies: Evidence from Nepal and Ghana - Takeshima, Hiroyuki; Liu, Yanyan (Elsevier, 2020)
Recent agricultural transformation in Asia and Africa has witnessed the gradual spread of mechanization in agricultural areas that are still largely made up of smallholder farming. While the literature has often characterized mechanical technologies as being complementary to land, knowledge gaps exist with regard to the process of adoption of mechanization by smallholders for whom the scope for exploiting its complementarity with land is limited. We test a hypothesis that yield-enhancing biological technologies—which potentially raise total factor productivity and returns to more intensive farm-power use—are important drivers of the adoption of agricultural mechanization among smallholders. To enhance the external validity of evidence, we empirically analyze this hypothesis by applying the same methodologies in two countries, lowland (Terai) Nepal and Ghana. We employ nationally representative, repeated, cross-sectional data from both countries, as well as unique tractor-use data from Ghana; we also employ multidimensional indicators of agroclimatic similarity in the respective plant breeding locations. We show that in both lowland Nepal and Ghana, the adoption of tractors and agricultural equipment has been induced by yield-enhancing biological technologies, particularly improved varieties and high-yielding production systems, when these biological technologies are instrumented by agroclimatic similarity to plant breeding locations, which is measured accounting for the multidimensional characteristics of agroclimatic conditions, and thus proxies spillover potentials of the public sector developed biological technologies. In general, these effects are particularly strong among smaller farms, and the effect holds for the adoption of mechanization both at extensive margins (whether to adopt) and at intensive margins (how much to adopt). In Ghana, partly due to improved efficiency in supply-side factors of mechanization, these linkages have strengthened in the 2010s. The results suggest that in both countries, mechanization support strategies for smallholders can potentially improve their targeting by utilizing the information of agroclimatic similarity with plant breeding locations. In Ghana, further public investments in plant-breeding system in strategic locations may broadly enhance smallholders' demand for mechanization. In lowland Nepal where tractor adoptions have grown fairly high, it is now important to more carefully evaluate the trade-off between smallholder-based growth strategies and other strategies, for example, promoting scale-expansions of farming, which also involves mechanization.